Thermo-ecological analysis of industrial kilns. (1st July 2019) - Caglayan, Hasan; Caliskan, Hakan
Abstract: In this study, thermo-ecological analysis has been applied by using ecologic objective function " E C O " and ecological coefficient of performance " E C O P " to the kilns used in the firing process of the ceramic plant. Five different environmental (dead state) temperatures (between 10 °C and 30 °C) are taken into account. The irreversibility, which are the most important criteria affecting ecological performance, occurs during the heat transfer in the burners and cooling in the kiln. The irreversibility and product exergy values are compared under different environmental temperatures. The ECO and ECOP values are inversely proportional to the environment temperatures. The maximum ECO and ECOP values are determined as −2387.156 kW and 0.051, respectively, while their corresponding minimum values are −2577.394 kW and 0.026, respectively. The results obtained can be a guide for the thermo-ecological design of industrial kilns. The losses of the kiln are high. It is necessary to reduce the losses to increase the performance and ecologic indicator results. The kilns are not environmentally benign at higher ambient temperatures. The optimum working condition of the kiln can be considered as 10 °C. Better insulations are necessary for the side, bottom and top surfaces of the kilns to reduce the losses. In this regard, the waste heat recovery for the gases can be taken into account for better efficiency and environmental assessment. Highlights: Ecologic objective function analysis is firstly applied to the industrial kilns. Ecological coefficient of performance analysis is firstly used for industrial kilns. Effects of environmental temperature on environmental assessment is investigated.